Arthroscopic treatment for Intraarticular knee infection in Hanoi Medical University Hospital - Hoan Tran Thanh; Dung Tran Trung; Thanh Ma Ngoc; Minh Ho Ngoc; Hung Pham Xuan; Tung Tran Son; Ban Hoang Van; Trinh Le Khanh; Phong Nguyen Duc (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2017)
Objectives: 1) Describe the arthroscopic image of infected osteoarthritis of knee; 2) Evaluate the result of arthroscopic treatment for infected osteoarthritis of knee Patients and method: Retrospective study 33 patients underwent arthroscopic treatment for infected osteoarthritis of knee in Hanoi Medical University Hospital from 2009 to 2013 Results: 1st stage of osteoarthritis occupied 36.4%; 45.5%, 12.1% and 6% for 2nd, 3rd and 4th respectively. According to Bussier classifi cation, the excellent and good result is 72.7%; moderate is 21.2% and bad result is 6.1%. Conclusion: Arthroscopic treatment for infected osteoarthritis of knee give good result.